Karakterisasi Bahan Feroelektrik Strontium Titanat (Srtio3) Dengan Menggunakan X- Ray Diffraction - Dewi, Rahmi; ', Krisman; ', Susilawati (Universitas Riau, 2012)
Ferroelectric material Strontium Carbonate (SrCO3) has been made with the comparison of 1:1 from chemicalreaction of Titanium Dioxide (TiO2). The pellet was anneled with the temperature of 700oC and thencharacterized using XRD. The XRD result of SrTiO3 after anneling showed some peaks, the positions of thepeaks on 2θ are 23.32°, 32.72°, 40.00o, 47.07o, 52.40°, 57.80o. After anneling, the peaks become wider, this meanthe samples become crystaline in structure. From the “a” value calculation “a” mean value obtained is 3,86 Å.Once the value of a calculated and a reference value obtained percentage error can be calculated that is 1.15%.